Bihasin kang mga Ati a history of loss tradition and disenfranchisement of the Ati from perspective of Pangrangso. - Senday, Aaron Richard C. (2016.)
There are several academic literatures regarding the alteration on the cultural practices of the indigenous peoples of the Philippines. These cultural practices are inclined to their environment ? thus, a change or disruption in their environment directly affects their culture. Phenomena such as globalization and commercialism are somewhat the major factor that triggers the reorganization of the indigenous peoples? cultures. Specifically, the Ati of Boracay Island had traditional living practices in order to make ends meet. This in the form of moving from one place to another, foraging resources along the way. Upon the proclamation of Boracay as a tourist zone in 1978, the island underwent a massive change due to the increasing number of population on non-Ati (Bisaya, in Inati term) and foreigners. This thesis argues that due to these changes, the living practices of Ati that are reliant to environment was greatly affected, thus leading to a drastic reorganization on the cultural attributes of the Ati. This thesis used Auguste Comte?s Sociocultural Evolution Theory and Emile Durkheim?s Division of Labor Theory. The researcher utilized Alicia Magos? Handum Kang Mga Ati: The Negritos (Ati) of Boracay Island, Malay, Aklan, an Ethnographic Report and Burial Grounds and Burial Practices: Indicators of Ati Indigeneity in Boracay Island (2005) for empirical data regarding the pangrangso culture. In addition, the researcher also conducted an interview with the Ati elders in order to obtain in-depth information about the pangrangso culture. This thesis proves that from semi-nomadic living practices which are characterized by moving and foraging from one place to another, the Ati?s living practices are now shifting based on a larger division of labor inside the island and due to restrictions imposed by land owners. This is manifested by several Ati engaging into several jobs such as boat crews, drivers, vendors, beggars and other similar jobs.
Research Paper (Undergraduate, Bachelor of Arts in History) College of Arts and Sciences,University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Ati -- Boracay, Aklan; Pangraso Culture; Ati -- Cultural practices